MENYIASATI TANTANGAN PELAKSANAAN PENELITIAN TINDAKAN KELAS - Rahmadani Fitri Ginting; Sabila Ramadhani; Indah Juniarti (Sindoro: Cendikia Pendidikan, 2024)
This study investigates the challenges encountered in implementing Classroom Action Research (CAR). Classroom Action Research has emerged as a significant method in education to enhance classroom learning quality. However, its implementation is often hindered by various challenges that can impact the research process. Therefore, a profound understanding of potential obstacles during CAR is crucial to assist researchers in overcoming these barriers and achieving their research goals more effectively. This paper highlights the importance of identifying and addressing various challenges that may arise during CAR implementation. By understanding and addressing these challenges, researchers are expected to conduct CAR more efficiently and successfully achieve optimal outcomes in efforts to improve classroom learning quality. The study employs a qualitative approach involving descriptive methods and literature review. By integrating descriptive methods, literature review, and qualitative approach, this research aims to provide an in-depth understanding of CAR implementation and identify and overcome potential challenges during the process.